Early Christian Definitions of Prophecy and DivinationA Reconsideration - Klingshirn, William (Studies in Late Antiquity, 2021)
It has often been maintained in biblical and early Christian scholarship that there is a qualitative difference between prophecy (προϕητεία, Lat. prophetia) and divination (μαντική, Lat. divinatio), the one a form of religion and therefore true, and the other a form of magic and therefore false. This view is well illustrated in Otto Böcher’s definition of prophecy (Weissagung), originally published in 2005 in the fourth edition of Religion in Geschichte und Gegenwart, and translated in Religion Past & Present in 2011:The phenomenon of predictive prophecy (Weissagung) is often referred to by the related terms “promise” (Verheißung) and “soothsaying” (Wahrsagung), which vary in content according to context. While soothsaying or divination (das Wahrsagen) belongs in the demonic sphere of an individual’s curiosity about his or her future, prophetic promise (Verheißung) is invariably understood as the prediction of eschatological and collective salvation; calamity is merely “predicted” (geweissagt), not “promised” (verheißen). The criteria offered by the Shepherd of Hermas (Herm. Mand. XI [43]) still apply: the divine Spirit inspires true prophets (Propheten) to foretell the truth, while false prophets and soothsayers respond to enquiries, for payment.1To be sure, the views expressed in this definition are not as widely held as they once were. Recent work in biblical and ancient near Eastern studies has sought to reclassify prophecy as a type of divination, in line with the classical definition that appears in Cicero’s De divinatione. This removes the possibility of prophecy being defined as a separate category, and a fortiori as a category opposed to divination.2 But however modern scholars choose to define the relationship between prophecy and divination, early Christian writers had their own views. Often these aligned with the interpretation that Böcher offers—indeed, they form the basis for it—but sometimes they did not. This paper raises the possibility that some early Christian texts proposed definitions of prophecy and divination that not only allowed for significant similarities between the two, but also made it possible for prophecy to replace divination as the general heading for the revelation of hidden knowledge, while at the same time reserving a place for the wide variety of methods that divination had traditionally included.It will help to begin by sketching out early Christian definitions of the boundary between prophecy and divination, particularly how hard or soft a boundary it was, and what consequences followed from this assessment. Nearly all early Christian writers defined prophecy, on the one hand, as the revelation of unseen knowledge that came from God and was unerringly true, and divination, on the other hand, as the disclosure of information that came from demons and was at best only partially true.3 But not all saw a hard boundary between the two, such that prophecy and divination involved essentially different kinds of operations. Instead, some early Christian writers appear to have seen prophecy and divination as the same kind of operation, differing only by source—the one divine, the other demonic—or by degrees of truth, from absolutely true to totally false. The importance of the distinction is that a hard boundary admitted little or no continuity between divination and prophecy, even where it was absolutely obvious, while a soft boundary acknowledged these continuities. A hard boundary tended to limit the practice and interpretation of prophecy to a few approved forms (dreams, lots), while a soft boundary admitted many practices that could be called prophecy, but were not perceptibly different from what had previously been considered divination (the many types described in Cicero’s treatise on divination, e.g.). If the main criterion for identifying the legitimacy of revealed knowledge was truth, then after centuries of disparaging divination, prophecy would simply have been a more accurate label for what was taken as revealed truth. Analyzing a few representative texts here will allow us to see how enlarging the category of prophecy in this way may have provided an ancient warrant for reclassifying Christian divination under a more acceptable name.To understand the roots of an early Christian distinction between prophecy and divination, we begin with a well-known passage from the Septuagint version of Deuteronomy 18. In the words of Moses,9 If you come into the land that the Lord your God gives you, you shall not learn to act in accordance with the abominations of those nations. 10 There shall not be found among you anyone purifying his son or daughter in fire, performing divination (μαντευόμενος μαντείαν), observing omens, and divining from birds (κληδονιζόμενος καὶ οἰωνιζόμενος), a sorcerer (ϕάρμακος), 11 anyone chanting a spell (ἐπαείδων ἐπαοιδήν), a belly talker and observer of portents (ἐγγαστρίμυθος καὶ τερατοσκόπος), or anyone consulting the dead (ἐπερωτῶν τοὺς νεκρούς). 12 For everyone doing these things is an abomination to the Lord your God…14. For these nations, those whom you will take into your possession, will listen to omens and divinations (κληδόνων καὶ μαντειῶν), but to you the Lord your God did not grant this. 15 The Lord your God will raise up a prophet like me from among your brothers (προϕήτην ἐκ τῶν ἀδελϕῶν σου ὡς ἐμὲ). You shall listen to him.4In the preface to book 5 of his Demonstratio evangelica, Eusebius translates these prescriptions into a Roman imperial context:For, as I said in the Preparatio evangelica, the Greek philosophers and prose writers themselves have testified to these things. They have very convincingly shown demons in their wickedness perverting the human race with crafty tricks, sometimes involving oracles (τοτὲ μὲν ταῖς διὰ μαντειῶν), and sometimes birds or portents or sacrifices, or similar things (τοτὲ δὲ ταῖς δι’ οἰωνῶν ἢ συμβόλων ἢ θυμάτων ἢ τῶν παραπλησίων). For this reason, one must declare that their oracles (τὰ χρηστήρια) do not belong to the supreme God. Therefore, it would not be permissible to compare these with the prophets of the Hebrews (οὐδὲ συγκρίνειν αὐτὰ τοῖς Ἑβραίων προϕήταις θεμιτὸν ἂν εἴη), whose first teacher of sacred truths and theologian was Moses (Eus. Demonstr. evang. 5.pr. 19–20).5Thus arises the view, deeply persistent in the Christian tradition, that prophecy is not a form of divination at all, but divine wisdom of a different order. By being incomparable with divination, prophecy must be taken to belong to another category altogether: it would then be categorically different.6 And as Scott Berman has pointed out, “If things belong to different categories, then comparing them is meaningless as they have no thing in common in virtue of which to compare them.”7A particularly clear statement of this distinction can be glimpsed in pseudo-Clement, Homily 3, which identifies the difference between the one true Prophet and those who merely make predictions, such as physicians and diviners.For physicians predict things, using the patient’s pulse as the material submitted to them, and others make predictions by birds, by sacrifices, and by many other different means submitted to them (καὶ οἱ μὲν πτηνά, οἱ δὲ θύματα, καὶ ἄλλοι ἄλλας ὕλας πολλὰς διαϕόρους ὑποβεβλημένας ἔχοντες), but prophets they are not. If someone should wish to say that a prediction made by such methods is similar (ὁμοίαν) to the foreknowledge that is, in essence, implanted (τῇ ὄντως ἐνϕύτῳ προγνώσει), he would be much deceived. For he only discloses such things as are present, and that is if he speaks the truth…The foreknowledge of the one true prophet does not only understand present things, but also extends prophecy without limit even to eternity itself. It needs no interpretation, prophesying obscure and ambiguous things, so that one needs another prophet to understand the things that have been said. Rather, it is simple and literal, just as our teacher, a prophet by the inborn and ever flowing spirit (ἐνϕύτῳ καὶ ἀεννάῳ πνεύματι), always knew all things (ps.-Clem. Hom. 3.11–12).8Such views are very far from the prevailing Greek and Roman taxonomy, well expressed by Cicero in De divinatione, that divination is the heading under which all its forms, including inspired types such as prophecy, but also technical types such as augury, are comprehended.9 Eusebius explains this view before taking issue with it in the Demonstratio evangelica:Greeks and barbarians make mention of the existence of divination and oracles everywhere on earth. These, they say, were introduced by the providence of the Creator for the use and benefit of humankind. in such a way that there is no difference (μηδὲν…τὸ διαϕέρον) between the prophets of the Hebrews and the oracles (χρηστήρια) of the rest of the nations. For they say that just as the Supreme God makes divinatory proclamations and offers beneficial things to the Hebrews through such prophets, so he does to the other nations through the forms of divination in each region…[Just as he does with other goods], so also does the Creator abundantly supply an understanding of the foreknowledge of the future to all humans, to some through men serving as prophets (τοῖς μὲν διὰ προϕητῶν ἀνδρῶν), to others through oracles (τοῖς δὲ διὰ χρηστηρίων), and to others through the flight of birds, sacrifice, the sending of dreams, through omens, twitches, or other chance occurrences (τοῖς δὲ δι’ ὀρνίθων πτήσεως, ἢ διὰ θυτικῆς, ἢ δι’ ὀνειροπομπείας, ἢ διὰ κληδόνων, ἢ παλμῶν, ἤ τινων ἑτέρων συμβόλων). For they say that these have been bestowed upon humankind by the providence of God in such a way that the prophets of the Hebrews appear to have no more (Eus. Demonstr. evang. 5.pr. 3–5).10As already noted, Eusebius did not accept this taxonomy, in large part because of a strongly held view that the gods of the Greeks and Romans were in actuality wicked demons that wanted nothing but the worst for humans and that none of their predictions could come from God. And he was not of course alone: a large number of writers agreed, both in his own day and for a long time afterward, even up to the present. But did all Christians hold to such a boundary? A few examples will present alternative classifications.Prior to the year 400, Augustine was much more sympathetic to a divinatory view of divine providence than in his later years. In a sermon he delivered in the early 390s, shortly before his ordination as bishop in 394, he surveyed the modes of divine communication in what looks very much like a classification of the forms of Christian divination:Now there are many ways in which God speaks with us. At times he speaks through an instrument, as through a codex of the divine scriptures (per codicem divinarum scripturarum). He speaks through a heavenly body, as he spoke to the Magi through a star (per stellam)…He speaks through a lot (per sortem), just as he spoke concerning the choice of Matthias in place of Judas. He speaks through the human soul (per animam humanam), as through a prophet (per prophetam). He speaks through an angel (per angelum), just as we understand him to have spoken to certain patriarchs and prophets and apostles. He speaks through a creature (per…creaturam) endowed with speech and sound, just as we read and believe of voices produced from the heavens, although no one is visible to the eye. Finally, God speaks directly to a person, not externally through the ears or eyes, but internally in the soul, and not in one way only, but in dreams (in somnis)…or with a person’s spirit lifted up (spiritu hominis assumpto), which the Greeks call ecstasis…or in the mind itself (in ipsa mente), when each person understands his majesty and his will (Serm. 12.4).11The scriptures, the stars, lots, prophecies, dreams, ecstatic revelations—all of these had a claim to be Christian forms of divination, and they differed, as Augustine believed, not so much in kind from pagan divination, as in degree. For the demons could reveal hidden information and even make predictions, as he admitted, that sometimes were true. His De divinatione daemonum, written in the early fifth century, explains how that could be, for example because demonic bodies were very light and fast. But it also assures his readers of the vast superiority of God’s prophecies: “By this and similar abilities, demons foretell many future things. But they are far below the height of prophecy that God effects through the holy angels and prophets.”12 To be sure, God’s prophecies were always completely true (veracissima).13 Nevertheless, divine and demonic predictions both belonged to the same continuum of true information; they were not of two different kinds: “Demons also hear and predict some such things [in the same manner as angels]…but it does not in any way hinder, but rather promotes the greater knowledge and glory of truth, when those who contradict it by their wicked character tell what they know about it.”14 Augustine’s view of the disclosure of hidden information—even when demons were responsible—was thus respectful of classical definitions of divination, in which all kinds were comprehended.Origen appears to have held a similar position. In a comment on 1 Corinthians 14:6, he defined prophecy as follows: “Prophecy is the science of signifying things that are unseen by means of language” (Προϕητεία ἐστὶν ἡ διὰ λόγου τῶν ἀϕανῶν σημαντικὴ).15 As Caroline Bammel observed in 1989, this definition remains silent on the source of the prophecy.16 Except for its limitation to language, it could almost be a definition of divination. Its implications for Origen’s understanding of the relationship between Hebrew prophecy and pagan divination can be seen in his discussion in Contra Celsum of the passage quoted above from Deuteronomy:“The nations,” as it is in fact written in the very law of the Jews, “will listen to omens and divinations,” whereas to that people it was said, “but to you the Lord your God did not grant this.” and it is said in addition to this that “The Lord your God will raise up for you a prophet from among your brothers.” While the nations therefore were using “divinations,” whether through “omens” or augury, or birds, or belly-talkers, or even those offering sacrifice or Chaldaean horoscope casters, these were the very things that had been forbidden to Jews. But if indeed the Jews had no consolation in the form of knowledge of the future, then being led by the human appetite for knowledge of the future, they would not have paid any attention to their own prophets on the grounds that they had nothing divine in themselves, and would not have accepted a prophet after Moses, nor recorded their words. Rather, they would on their own have changed to the divinations and oracles of the nations, or would have tried to establish some such thing also among themselves. So it is not strange that the prophets among them made predictions concerning everyday things for the consolation of those who longed for such things, with the result that Samuel prophesied even concerning lost asses and concerning the disease of the king’s child, as written in the third book of Kings.17The difference from pagan diviners was not in the nature of what was predicted, but the source, what Origen in a subsequent book of contra Celsum called “God’s divine spirit in Moses” (ὑπὸ τοῦ ἐν Μωϋσεῖ θείου πνεύματος). “For,” as in the well-known line from Homer, “he ‘knew the things that exist and those that will be and those that existed before’ (Iliad 1.70) better than the diviners (μάντεων) said by the poets to have known them.”18 Moses was no different than “Chalcas, son of Thestor, by far the best of bird-diviners” (Iliad 1.69), save for the source of his inspiration and the degree of his knowledge. What he predicted and how he predicted were the same.Our final example is drawn from the preface to an anonymous commentary on Jeremiah. Although it is attributed to John Chrysostom, Léon Dieu argued that it was likely not by him, but by a later author, perhaps Polychronius of Apamea, brother of Theodore of Mopsuestia and author of catenae on Job, Daniel, and Ezechiel.19 The preface offers a comprehensive Christian classification of prophecy, a large part of which was incorporated into the definition of prophecy in the Suda, s.v. prophēteia (π 2923): “Now in general, [there are four kinds] of prophecies. The first is spiritual (πνευματική), the second diabolic (διαβολική), the third, between these, is natural (ϕυσική) or technical (τεχνική), and the fourth is common (κοινή) and popular (δημώδης).”20The third and fourth types, as Ps.-Chrysostom explains them, consist of non-divinatory predictions and can therefore be quickly dispensed with. The third type includes a natural kind that belongs to animals, such as the fact that ants know when winter is approaching, and an artificial kind, such as the predictions made by physicians, advisers, and ship captains. The fourth type overlaps with this and indicates a kind of ordinary foreknowledge that all people have, such as that “after three months comes winter.”The first two types, on the other hand, labeled as spiritual and diabolic, are both prophetic, as the text says, or, as we might say, divinatory. This is because, as the author indicates, both pagans and Christians call their prophets by the same name, citing Paul’s Letter to Titus: “It was one of them, their very own prophet, who said ‘Cretans are always liars, vicious brutes, lazy gluttons’” (Titus 1:12, NRSV). The author’s main goal, therefore, is to distinguish the spiritual kind from the diabolic kind. The spiritual kind, he says, is mainly practiced by those who are holy, although sometimes not, as in the case of the dreams of Nebuchadnezzar (Daniel 2) and Pharaoh (Genesis 41), and the prophecies of Balaam (Numbers 22–24; 25:1–9; 31:8, 16), and Caiaphas (John 11:50–51). Spiritual prophecy is also said to occur not only when the prophets are asked, as it is with pagans, but also on their own. And spiritual prophecy has as its purpose a reform of character and repentance, unlike pagan prophecy, which is mainly about property, diseases, and wars. Furthermore, while pagan prophecy requires instruments, special places, and proper times, and pagan prophets speak for money, spiritual prophecy is free of all of this. Spiritual prophecy, finally, occurs through virtue (δι’ ἀρετῆς), whereas pagan prophecy occurs through an evil technique (διά τινος κακοτεχνίας).Diabolic prophecy, on the other hand, speaks the truth only by chance (κατὰ συμβεβηκὸς). As its name indicates, it is operated by servants of the devil. It responds to questions, requires special conditions, and costs money. But despite being far inferior to spiritual prophecy, demonic prophecy was still classified as prophecy. It was not so different that it needed a different name. In the second century CE the dream interpreter Artemidorus had classified diviners along a similar spectrum.21 The most reliable, in his view, were bird diviners, dream interpreters, and those who interpreted signs from sacrifices, portents, and meteorological phenomena. Those who cast horoscopes received a less robust endorsement. At the other end of the spectrum were necromancers and those who divined from knucklebones, sieves, and other common objects. Everything they said was “false and without foundation” (ψευδῆ πάντα καὶ ἀνυπόστατα), and they had no knowledge of divination (καὶ αὐτοὶ μὲν μαντικῆς οὐδὲ βραχὺ ἴσασι). But even so, Artemidorus did not apply a different name to such figures. Rather, he attacked them precisely because they appeared as diviners to others, and therefore constituted a threat to his own profession.22 We could say that ps.-Chrysostom was doing something similar, and perhaps for similar reasons. The main difference is that rather than evaluating various types of mantikē, it was the varieties of prophēteia that he was concerned to distinguish. And in that way, the category of prophecy replaced the category of divination.If we were to examine, instead of the Christian prescriptions discussed here, the actual divinatory practices in which Christians engaged, we would find a very high level of continuity between classical and early Christian methods of divination. A few kinds would have been impossible for Christians—for instance, those requiring animal sacrifice or performed through (or at the shrine of) a pagan divinity—but most kinds were not, including both the inspired types that could include prophecy and dreams and technical varieties such as astrology. It appears that early Christian descriptions of a broadly defined prophecy that included some or all of these types—that is, those that demonstrate a soft boundary between Christian and classical forms—are simply more trustworthy witnesses to the past than those that rejected most forms of “divination” because, falling outside a narrowly defined category of prophecy, they could not be considered authentic forms of divine communication. Contemporary historical and theological evaluations of ancient Christian views of divination and prophecy should be at least as willing as our sources to describe the performance of many forms of divination (or prophecy) as Christian. Doing so would allow us to examine the division between prophecy and divination as a subject of ancient debate and disagreement, but not necessarily as a meaningful or reliable template for modern scholarship.